RECLAIMING AGENCY: AN ECO-FEMINIST ANALYSIS OF FEMALE EMPOWERMENT IN ‘36 VAYATHINILEY’ - Sridevi. T; Balaraman.S (The Bioscan, 2024)
This article presents an eco-feminist analysis of the Tamil film ’36 Vayathiniley’ (2015), exploring the intersections of female empowerment, environmental degradation, and patriarchal oppression. Through critically examining the film’s narrative, characters, and themes, this study demonstrates how the protagonist’s journey toward self-discovery and agency is inextricably linked to her relationship with the natural world. By reclaiming her agency, the protagonist challenges the dominant patriarchal structures that perpetuate environmental degradation and oppression. This research contributes to the growing body of eco-feminist scholarship, highlighting the importance of intersectional approaches to understanding the interconnectedness of social and environmental justice.